Titrimetric assay of lisinopril in aqueous and non-aqueous media - Kanakapura, Basavaiah; Tharpa, Kalsang; Vinay, Kanakapura Basavaiah (Eclética Química, 2010)
Four simple titrimetric procedures are described for the determination of lisinopril (LNP) in bulk and in pharmaceuticals based on the neutralization of basic-amino and acidic carboxylic acid groups present in LNP. Method A is based on the neutralization of basic amino groups using perchloric acid as titrant in anhydrous acetic acid medium. Method B, method C and method D are based on neutralization of carboxylic acid group using NaOH, sodium methoxide and methanolic KOH, as titrants, respectively. Method A is applicable over 2.0-20.0 mg range and the calculations are based in the molar ratio of 1:2 (LNP:HClO4). Method B, method C and method D are applicable over 2.0-20.0 mg, 1.0-10.0 mg and 5.0-15.0 mg range, respectively, and their respective molar ratios are 1:1 (LNP:NaOH), 1:2 (LNP:CH3ONa) and 1:1 (LNP:KOH). Intraday and inter day accuracy and precision of the methods were evaluated and the results showed intra- and inter-day precision less than 2.7% (RSD), and accuracy of < 2.5% (RE). The developed methods were applied to determine LNP in tablets and the results were validated statistically by comparing the results with those of the reference method by applying the Student’s t-test and F-test.